Victorian evolution of inherited retinal diseases natural history registry (VENTURE study): Rationale, methodology and initial participant characteristics. (12th June 2022) - Britten‐Jones, Alexis Ceecee; O'Hare, Fleur; Edwards, Thomas L.; Ayton, Lauren N.; ,
Abstract: Background: Emerging treatments are being developed for inherited retinal diseases, requiring a clear understanding of natural progression and a database of potential participants for clinical trials. This article describes the rationale, study design and methodology of the Victorian Evolution of inherited retinal diseases NaTUral history REgistry (VENTURE), including data from the first 150 participants enrolled. Methods: VENTURE collects retrospective and prospective data from people with inherited retinal diseases. Following registration, participants are asked to attend a baseline examination using a standardised protocol to confirm their inherited retinal disease diagnosis. Examination procedures include (i) retinal function, using visual acuity and perimetry; (ii) retinal structure, using multimodal imaging and (iii) patient‐reported outcomes. Participants' molecular diagnoses are obtained from their clinical records or through targeted‐panel genetic testing by an independent laboratory. Phenotype and genotype data are used to enrol participants into disease‐specific longitudinal cohort sub‐studies. Results: From 7 July 2020 to 30 December 2021, VENTURE enrolled 150 registrants (138 families) and most (63%) have a rod‐cone dystrophy phenotype. From 93 participants who have received a probable molecular diagnosis, the most common affected genes are RPGR (13% of all registrants), USH2A (10%), CYP4V2 (7%), ABCA4 (5%), and CHM (5%). Most participants have early to moderate vision impairment, with over half (55%) having visual acuities of better than 6/60 (20/200) at registration. Conclusions: The VENTURE study will complement existing patient registries and help drive inherited retinal disease research in Australia, facilitating access to research opportunities for individuals with inherited retinal diseases.